Rice bran oil-in-water optimized emulsions for the development of plant-based foods and beverages - Benitez, Lucas Osvaldo (2024)
Aim: This work aimed to develop rice bran oil-in-water (O/W) emulsions, stabilized with different mixtures of pea protein concentrate (PPC), Arabic gum (AG), and maltodextrin (MD), as the basis for the formulation of plant-based food products. Methods: The effects of the aqueous phase formulation on the properties of the resulting O/W emulsions were evaluated by a mixture design approach. Volume-weighted mean diameter (D[4,3]) of the emulsion particles and polydispersity expressed as the difference of D[4,3] – D[3,2], apparent viscosity at a shear rate of 200 s–1 and backscattering at different times associated to the global stability of the emulsions were studied as response variables. A multi-response optimization was carried out and mathematical models were validated. Results: The ternary mixtures of the aqueous phase showed significant antagonism between the three components in all the response variables. The optimal formulation of the aqueous phase for the O/W emulsions obtained after three homogenization cycles was 78% PPC and 22% MD. The properties of the O/W optimal emulsion were according to the ones predicted by the model. Conclusions: The best-formulated emulsion is promising for developing plant-based foods and beverages.